Evaluasi Penerapan Peraturan Kepala Arsip Nasional Nomor 7 Tahun 2017 Tentang Gerakan Nasional Sadar Tertib Arsip Di Lingkungan Kementerian Perindustrian Tahun 2019 - Isnaeni Yuliani (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2021)
The purpose of this study is to evaluate the implementation of the Regulation of the Head of the National Archives Number 7 of 2017 concerning the National Movement for Archival Discipline Awareness at the Ministry of Industry. This research also aims to find out what obstacles are faced so that they can be used as a reference in formulating strategies as an effort to optimize the implementation of GNSTA within the Ministry of Industry. In this study the authors used descriptive qualitative research. Data collection techniques include observation, interviews, and documentation. The informants were selected using a purposive method involving the Head of the Archives Subdivision, Archives, Archives Manager, and also the community. The data analysis technique used data reduction techniques, data presentation, then drawing conclusions while the data validity techniques used were validity and data triangulation. In analyzing the public policy evaluation theory, according to William Dunn. The results showed that the evaluation of the implementation of the Head of the National Archives Number 7 of 2017 concerning the National Aris Awareness Movement at the Ministry of Industry was quite good, but there were still some obstacles related to the quality of human resources and the number of archivists in the Ministry of Industry